P‐179: Enhanced Light Extraction from Organic Light‐Emitting Diodes using a Quasi‐periodic Nanostructure. Issue 1 (2nd June 2017) - Lee, Ju Sung; Shim, Yong Sub; Park, Chan Hyuk; Hwang, Ha; Kim, Jae Geun; Joo, Chul Woong; Sung, Woo Jin; Lee, Jonghee; Park, Young Wook; Ju, Byeong-Kwon
Abstract : Here, we fabricate organic light‐emitting diodes (OLEDs) with quasi‐periodic nanostructure (QPS) processed both by laser interference lithography (LIL) and reactive ion etching (RIE). The LIL process is used for forming periodic pattern, and on the periodic pattern, the RIE process is supplemented for adding random property. The resulting quasi‐periodic nanostructure is composed of the silicon dioxide (SiO2 ) having low refractive index, and we were able to obtain enhanced light extraction characteristics of OLEDs in all viewing angle without any spectrum distortion problem, by utilizing each optical advantage of periodic and random structure.